Bullous Pemphigoid Arising in Lower Leg Vein Graft Incision Site. Issue 1 (27th November 2015) - Murphy, Bryan; Walsh, Maureen; McKenna, Kevin
Abstract: Bullous pemphigoid is a blistering disorder which can be idiopathic or arise secondary to drugs or trauma; however, blistering arising within surgical scars is rare. We present a patient with no prior skin history who developed blistering in his left calf vein harvesting scar soon after coronary artery bypass surgery. doi: 10.1111/jocs.12668 (J Card Surg 2016;31:57–59)